Understanding failure localization in mesh networks - Sun-il Kim; Lumetta, S.S. (Optical Fiber Communications Conference: Post Conference Digest, 2002)
We introduced a model for node failures and presented measures that effectively address node protection and failure localization. Results of our investigation show advantages of generalized loopback over ring-based algorithms in robustness and spare capacity in addressing node recovery and multiple failures compared to double cycle cover.